P147 Deprivation is associated with increased healthcare utilisation in patients with chronic obstructive pulmonary disease. (16th November 2010) - Collins, P F; Stratton, R J; Kurukulaaratchy, R; Elia, M
Abstract : Deprivation assessed using the index of multiple deprivation (IMD) has been shown to be an independent risk factor for 1-year mortality in outpatients with chronic obstructive pulmonary disease; COPD (Collins et al, 2010). IMD combines a number of economic and social issues (eg, health, education, employment) into one overall deprivation score, the higher the score the higher an individual's deprivation. Whilst malnutrition in COPD has been linked to increased healthcare use it is not clear if deprivation is also independently associated. This study aimed to investigate the influence of deprivation on 1-year healthcare utilisation in outpatients with COPD. IMD was established in 424 outpatients with COPD according to the geographical location for each patient's address (postcode) and related to their healthcare use in the year post-date screened (Nobel et al, 2008). Patients were routinely screened in outpatient clinics for malnutrition using the 'Malnutrition Universal Screening Tool', 'MUST' (Elia 2003); mean age 73 (SD 9.9) years; body mass index 25.8 (SD 6.3) kg/m 2 with healthcare use collected 1 year from screening (Abstract P147 Table 1 ). Deprivation assessed using IMD (mean 15.9; SD 11.1) was found to be a significant predictor for the frequency and duration of emergency hospital admissions as well as the duration of elective hospital admission. Deprivation was also linked to reduced secondary care outpatient appointment attendance but not an increase in failure to attend and deprivation was not associated with increased disease severity, as classified by the GOLD criteria (p=0.580). COPD outpatients residing in more deprived areas experience increased hospitalisation rates but decreased outpatient appointment attendance. The underlying reason behind this disparity in healthcare use requires further investigation. Collins P.F. et al, (2010) presented at BTS winter meeting (SP165). Stratton RJ, et al, (2003) Disease-related malnutrition, CABI publishing; Elia M (Ed.) (2003) The 'MUST' report. BAPEN, Redditch (www.bapen.org.uk ); Nobel et al, (2008) The English indices of deprivation 2007 (www.communities.gov.uk ).